MODAL QUALIFIERS AS BOOSTER IN ARGUMENTATIVE WRITING OF THE THESIS DISCUSSION SECTION (MODAL QUALIFIERS SEBAGAI BOOSTER DALAM TULISAN ARGUMENTATIF PADA BAGIAN PEMBAHASAN TESIS) - Yuliana Setyaningsih; R. Kunjana Rahardi; Refa Lina Tiawati (Jurnal Gramatika, 2023)
The importance of using modal qualifiers as a component of argumentative writing in the discussion section of student theses has not been fully realized by students. In fact, this component greatly determines the level of strength of the argument as a vehicle for conveying scientific truth. Scientific truth can be tested through the strength of the argument that appears in the selection of the types of modal qualifiers that accompany the position statement. This study aims to describe the manifestation of the form and function of the modal qualifier as a booster in argumentative writing for thesis discussion. The research data is in the form of excerpts of claims which contain boosters from the thesis discussion section of students of the Indonesian Language Education Master’s Program at Sanata Dharma University, Yogyakarta. Data was collected by listening method with note-taking technique. Furthermore, the stages of classification and typification of data are carried out. The analytical method used in this study is the distributional analysis method and the content analysis method. The results of this study are the following forms of capital qualifiers as boosters: (1) definitely, (2) necessary, (3) must, (4) certainly, and variations in form. This study also found seven booster functions as follows: (1) affirming by showing confidence, (2) affirming by giving recommendations, (3) affirming by confirming something, (4) affirming by confirmation of clarity, (5) affirming by inferring purpose, (6) affirming of intent by ensuring, (7) affirming by suggesting something.